Highly solvent-stable polyimide ultrafine fibrous membranes fabricated by a novel ultraviolet-assisted electrospinning technique via organo-soluble intrinsically negative photosensitive varnishes - L. Qi; C. Y. Guo; M. G. Huangfu; Y. Zhang; L. Wu; X. X. Zhi; J. G. Liu; X. M. Zhang (eXPRESS Polymer Letters)
A novel fabrication methodology for polyimide (PI) UFMs based on soluble PIs with high solvent durability was developed. As fiber-forming agents, a series of intrinsically negative photosensitive polyimides (PSPIs) with solubility in organic solvents were synthesized by the one-step thermal polymerization of 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA) with three ortho-alkyl-substituted diamine monomers, namely, 3,3′,5,5′-tetramethyl-4,4′-diaminodiphenylmethane (TMMDA, for PI-1), 3,3′-dimethyl-5,5′-diethyl-4,4′-diaminodiphenylmethane (DMDEDA, for PI-2), and 3,3′,5,5′-tetraethyl-4,4′-diaminodiphenylmethane (TEMDA, for PI-3), respectively. Electrospun UFMs were prepared by both traditional electrospinning (PI UFMs) and the novel ultraviolet-assisted electrospinning (UVAES) method (PI-UV UFMs). The effects of the fabrication method on the physical and chemical properties of the electrospun UFMs were investigated systematically. High-efficiency photoinduced crosslinking reactions under ultraviolet (UV) radiation provided the PI-UV UFMs with considerable thermal dimensional stability with the 5% weight loss temperature over 440 °C. Meanwhile, the derived PI-UV UFMs showed excellent resistance against a polar aprotic solvent, N,N-dimethylacetamide (DMAc).